Rancangan Animasi Media Pembelajaran Bahasa Inggris Ke Indonesia Untuk Anak Usia Dini Berbasis Adobe Flash - Maulana, Riyan; Ismi, Risma Zaizafun; Lidiana, L (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Information technology is used to control data, process, obtain, organize, store, and manipulate data to produce quality information. Humans cannot be separated from education, which is education is an informal activity. Education is important at the early age of children is English. English is one of the international languages used to communicate throughout the world. Also, interactive and interesting learning media can help to attract children's interest in learning. Therefore, this research was conducted to produce an interactive design English learning media to Indonesian at an early age young learners using Adobe Flash.